Fluid inclusion and δ18O isotope values of fluids responsible for mineralization in the Hope Reef and Main Reef Complex of the Fairview Mine, Barberton, South Africa - Comuso, Christina Marie (Stellenbosch : Stellenbosch University, 2020)
Thesis (MSc)--Stellenbosch University, 2020.